Meningkatkan Performa dan Stabilitas Kecepatan Transfer Data pada FreeBSD dengan Kostumisasi Kernel - Handy Sunjaya; Deny Setiawan; Sandri Pratama (Universitas Multimedia Nusantara, 2013)
In this project, we demonstrated how to improve transfer rate when transfering data from a notebook installed FreeBSD operating system to another notebook installed Windows 8 operating system. The method which we used was with customizing the kernel on FreeBSD. Before we customized the kernel, we calculated the average time of the transfer speed with its default kernel. After we got the average time, then we customized its kernel and calculated the average time after we installed the custom kernel. At the end we got faster average time with the customized kernel and the performance better. Index Terms - FreeBSD, Server, Transfer rate, Improving